Competencies of nurses to participate in safe medication management practices for biologics: A scoping review - Wansheng Li; Li Li; Linbo Li; Cardenas Xiaodong; Mudiao Chen; Hongye Liu; Peirao Li (PLoS ONE, 2025)
Aim To review the existing literature relating to nurse competence in safe medication management practices for biologics, identify evidence, and develop a competency framework to clarify the role of nurses in these practices. Background With the widespread use of biological agents in disease treatment, ensuring the safe and economical use of high-cost medicines is particularly important. Even though nurses are essential in patient care, detailed knowledge regarding their competence and role in the safe administration of biologics is lacking. Design and methods A scoping review was performed following the methodology of Arksey and O’Malley and the PRISMA ScR guidelines. Electronic databases, including PubMed, CINAHL, Embase, Scopus, and Web of Science, were searched using accepted keywords, and relevant articles were identified using inclusion and exclusion criteria. Results A total of 3,422 studies were retrieved, 24 of which were eligible for inclusion. The required competencies for nurses were summarized into six areas: clinical specialized knowledge, critical thinking and problem-solving skills, safe medication skills, health education skills, communication and coordination skills, and technological literacy. Conclusion We provide insights into the competencies of nurses involved in the safe medication management of biologics. These competencies can be used to assess the actual competency level of nurses and facilitate the maximization of biological treatment goals and outcomes. This plays a vital role in optimizing the use of healthcare resources and demonstrating outcomes.